Infection intensity shapes specialization and beta diversity of haemosporidian–bird networks across elevations - Karla Rodríguez‐Hernández; Paulina Álvarez‐Mendizábal; Leonardo Chapa‐Vargas; Federico Escobar; Wesley Dáttilo; Diego Santiago‐Alarcon (Ecosphere, 2023)
Abstract Host–parasite distribution and interactions depend on geography, evolutionary associations, species composition, and their response to environmental variables. In this sense, host specificity as a key parasite's life history trait may determine parasite community composition but can be difficult to identify in nature. The haemosporidian–avian host communities of tropical mountain systems offer an opportunity to better understand how network interactions influence parasite–host specialization. By using frequency (i.e., prevalence) and interaction intensity (i.e., number of parasites per infected host) data, we calculated two quantitative indices to evaluate haemosporidian host specialization at both community (H2′) and haemosporidian lineages and bird species levels (d′). Additionally, we evaluated alpha (SI) and beta diversity (βWN) of haemosporidian–bird interactions along four distinct elevations (representing different vegetation types) in Central Veracruz, Mexico. We recorded 607 birds from 88 species in two sampling years, registering 78 haemosporidian cytochrome b lineages by PCR in 125 positive samples from 38 bird species. Haemosporidian–bird interactions showed high specialization and modular network structure for each vegetation type. The degree of specialization and modularity was stronger when considering interaction intensity (i.e., parasitemia). Species‐level specialization was higher for birds than for haemosporidians at the two vegetation types with highest interaction richness (i.e., pine–oak forest and tropical deciduous forest). There were high interaction beta diversity values (~1) among vegetation types, reflecting turnover in both avian and parasite communities. Our findings suggest that vegetation type (proxy for the local environmental conditions) constrains the distribution of hosts and parasites, and that intraspecies infection intensity plays an important role in the transmission dynamics and interactions of the haemosporidian community.